Eating ethics of student life / Ariff Aiman Azmin Mustam... [et al.] - Azmin Mustam, Ariff Aiman; Mohammad Tahir, Nur Hidayah; Mohamad Saufi, Nurfarahah; Asramizan, Amirah Nuraini (2019)
According From Wikipedia Encyclopedia , Eating (also known as consuming) is the ingestion of food, typically to provide a heterotrophic organism with energy and to allow for growth. For humans, eating is an activity of daily living. Ethics means good behavior or ethical behavior that must be practiced while eating. Adab is the procedure or attitude in conducting a practice or act of Manners also means subtlety or moral character created in decency. Adab covers all forms of daily acts of deeds, including in the case of eating and drinking. As a Muslim, we are obliged to imitate the Prophet Muhammad in any case, including in terms of eating and drinking. We are encouraged to practice good ethics while eating because it reflects our character. So as the results eating and drinking of course use manners should be fulfilled. The purpose of doing this report is to describe how the students apply ethical eating in their daily life at the UiTM. It is to ensure if the students are following the rules that had been given to them such as put the plates that were used in the prepared place. Besides that, the report is being make to analyze that the students are always practicing ethics eating when they were eating at the cafe. This report provides an analysis and evaluation of the amount of manners or ethics while eating that all the students do.